Presence of Emissary Veins in the Glabellar Region in Metopic Craniosynostosis - Anna Sundelin; Erik Ceder; Madiha Bhatti‐Søfteland; Giovanni Maltese; Peter Tarnow; Lars Kölby; Karin Säljö (Clinical Anatomy, 2026)
ABSTRACT Emissary veins connect intra‐ and extracranial venous circulation by bridging the dural venous sinuses to the external veins of the skull. Their variable presence and location may have important implications in perioperative blood loss. Clinical observations and previous studies suggest that emissary veins are more frequently present in the glabellar region in patients with metopic synostosis and may serve as a source of bleeding during cranioplasty. This study investigated the presence of emissary veins in the glabellar region in patients with metopic synostosis. We retrospectively analyzed computed tomography scans for the presence of emissary veins in the glabellar region in all consecutive patients who underwent surgery for metopic synostosis or sagittal synostosis (controls) between 2020 and 2022 at the Craniofacial Unit at Sahlgrenska University Hospital. Among 86 patients included in the study (42 with metopic synostosis and 44 with sagittal synostosis), we identified emissary veins in the glabellar region in 90.5% of patients with metopic synostosis as compared with 11.4% of those with sagittal synostosis ( p < 0.001). These results suggest that emissary veins in the glabellar region are more frequently present in patients with metopic synostosis relative to age‐matched controls with a normal metopic suture, derived from our registry of patients with sagittal synostosis. This anatomical finding may explain the high perioperative blood loss observed during cranioplasty for metopic synostosis.